c/m :a) (a^2-b^2)^2+(2ab)^2=(a^2+b^2)^2 b) (a^2+b^2)(c^2+d^2)=(ac+bd)^2+(ad-bc)^2

Question

c/m :a) (a^2-b^2)^2+(2ab)^2=(a^2+b^2)^2
b) (a^2+b^2)(c^2+d^2)=(ac+bd)^2+(ad-bc)^2

in progress 0
Eloise 3 tuần 2021-08-17T05:04:37+00:00 1 Answers 3 views 0

Answers ( )

    0
    2021-08-17T05:06:32+00:00

    Đáp án:

    $\begin{array}{l}
    a){\left( {{a^2} – {b^2}} \right)^2} + {\left( {2ab} \right)^2}\\
     = {a^4} – 2{a^2}{b^2} + {b^4} + 4{a^2}{b^2}\\
     = {a^4} + 2{a^2}{b^2} + {b^4}\\
     = {\left( {{a^2} + {b^2}} \right)^2}\\
    b)\left( {{a^2} + {b^2}} \right)\left( {{c^2} + {d^2}} \right)\\
     = {a^2}{c^2} + {a^2}{d^2} + {b^2}{c^2} + {b^2}{d^2}\\
    {\left( {ac + bd} \right)^2} + {\left( {ad – bc} \right)^2}\\
     = {a^2}{c^2} + 2abcd + {b^2}{d^2} + {a^2}{d^2} – 2abcd + {b^2}{c^2}\\
     = {a^2}{c^2} + {a^2}{d^2} + {b^2}{c^2} + {b^2}{d^2}\\
     \Rightarrow \left( {{a^2} + {b^2}} \right)\left( {{c^2} + {d^2}} \right) = {\left( {ac + bd} \right)^2} + {\left( {ad – bc} \right)^2}
    \end{array}$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )